The influence of immigrant parent legal status on U.S.-born children's academic abilities: The moderating effects of social service use. Issue 4 (1st October 2016) - Brabeck, Kalina M.; Sibley, Erin; Taubin, Patricia; Murcia, Angela
ABSTRACT: The present study investigated the relationship between immigrant parent legal status and academic performance among U.S.-born children, ages 7–10. Building on previous research and a social ecological framework, the study further explored how social service use moderates the relationship between parent legal status and academic performance. Participants included 178 low-income, urban parent/child dyads; all parents were immigrants from Mexico, Central America, or the Dominican Republic and all children were U.S.-born citizens. Using a standardized academic assessment as the outcome, parent legal vulnerability was a significant negative predictor of children's academic performance on reading, spelling, and math subtests. Additionally, parent use of social services significantly and positively moderated the relationship between parent legal vulnerability and children's word reading and spelling skills, indicating that social service use can serve as a protective buffer against the negative associations between parental unauthorized status and child achievement.